Current knowledge about the hydrophilic and nanostructured SLActive surface - Wennerberg A; Galli S; Albrektsson T (Dove Medical Press, 2011)
Ann Wennerberg1,2, Silvia Galli2, Tomas Albrektsson2,31Department of Prosthodontics, Malmö University, Malmö, 2Department of Biomaterials, Gothenburg University, Gothenburg, 3Department of Materials Science and Technology, Malmö University, SwedenAbstract: This review summarizes the present documentation for the SLActive surface, a hydrophilic and nanostructured surface produced by Straumann Company in Switzerland, and covers the results from 15 in vitro, 17 in vivo, and 16 clinical studies. The SLActive surface is a development of the large grit-blasted and acid-etched SLA surface, and is further processed to a high degree of hydrophilicity. In general, the in vitro and in vivo studies of the SLActive surface demonstrate a stronger cell and bone tissue response than for the predecessor, the SLA surface, produced by the same company. However, in most studies, this difference disappears after 6–8 weeks. In the clinical studies, a stronger bone response was reported for the SLActive surface during the early healing phase when compared with the SLA surface. However, the later biological response was quite similar for the two surfaces and both demonstrated very good clinical results.Keywords: SLActive, surface, in vitro, in vivo, clinical results